The Decision to Become an Entrepreneur and the Firm Size Distribution: A Unifying Framework for Policy Analysis - Markus Poschke (Institute for the Study of Labor (IZA), 2013)
Developing and emerging economies have high entrepreneurship rates and relatively many small firms. There is enormous heterogeneity among these firms and entrepreneurs. This paper presents a simple occupational choice model that captures motives for entrepreneurship at both edges of the size distribution. The model is then used to analyse the effects of productivity growth, distortions, financial and labor market frictions, and risk. Capturing entrepreneurship across the size distribution allows for different reactions of high- and low-ability entrepreneurs to changes in policies and the environment. These may result in powerful general equilibrium effects. In particular, policies affecting high-ability entrepreneurs potentially running large firms can indirectly have a strong effect on entry by low-ability entrepreneurs and thus on the prevalence of small firms.
Keywords: J24; L26; O11; O17; 330; entrepreneurship; firm entry and exit; development; labor market regulation